Development of Interactive Multimedia Assisted of The HPLC Simulator to Enhance Student's Analytical Thinking Skills - Indah Karina Yulina; Anna Permanasari; Hernani Hernani; Wawan Setiawan (Chemistry Education Department, 2021)
This research aims to develop interactive multimedia by utilizing HPLC simulators to train students' analytical thinking skills, which will support dry lab practicum activities to be more meaningful. The research method is development research with a 4-D model design, defining, designing, developing, and disseminating. However, this research stage is limited to the development stage. The instruments used in this study include test and non-test instruments in student satisfaction questionnaires and observation of learning outcomes. The results showed that MMI assisted by an HPLC simulator helped students increase students' motivation and interest in studying HPLC material. In line with that, learning with the HPLC simulator can develop analytical thinking skills in the matching and classifying aspects, but has not trained in 3 other aspects, namely error analysis, generalizing, and specifying. It is recommended to use a learning approach such as STEM, which accommodates learning needs with the stages of inquiry, Engineering Design Process, and Product development to overcome the lack of development of analytical thinking skills in the aspects of analysis error, specifying, and generalizing.